Quba’ mosque: significance, history and architecture - Spahic, Omer (UNISSA Press, 2024)
This book is an attempt to bring the modern Muslim mind closer to understanding and appreciating the idea and the historical as well as architectural spectacle of the Quba’ mosque. The focus of the book is tripartite, drawing attention to the mosque’s religiosity, historicity and architecturality. The timespan covered by the discussion extends from the hijrah (migration from Makkah to Madinah) and the commencement of the Islamic civilizational presence in Madinah, till the current era. The most important episodes in the history of Islamic culture and civilization not only in the city of Madinah, but also beyond in the entire Hijaz region, and the most important protagonists, are encompassed. The primary sources consulted for the book were twofold: first, the classical history writings about Madinah where the authors as scholars and historians, sometimes even natives of the city of Madinah, were eyewitnesses to history; and second, a vast array of travel and exploration literature in which both Muslim and non-Muslim travellers and explorers participated. For each epoch of the history of the Quba’ mosque, a cluster of history and travel-cum-exploration authorities were relied on. This means that the book investigates the theme of the Quba’ mosque both “as it was” and “as it was seen”. The book is an analysis of a compendium of historical realities and human perceptions, tracking down where the two converged and where and why they separated. It follows that the title of the book - which is “Quba’ Mosque: Significance, History and Architecture” - in actual fact, implies the total religiosity, historicity and architecturality of the Quba’ mosque as witnessed, understood and reported at once by Muslim scholars, historians and travellers and non-Muslim travellers and explorers. That suggests that the book could as well be entitled “Quba’ Mosque in Historiography, Exploration and Travel Literature.” The book aims to capture and enliven the spirit that permeated the lengthy existence, plus the religio-historical performances, of the Quba’ mosque in its capacity as one of the foremost places of visitation in Madinah. The book furthermore intends to rationalize the revealed religious significance of the mosque, its dramatic albeit dictated-by-human-interferences historical trajectory, and its architectural kinetics whereby the form, predominantly, was influenced by the mosque’s established worth and functionality. In doing so, each side of the mosque’s multidimensional material and immaterial existence is given its due and is appreciated only for what it is. The mosque’s pure and unadulterated religiosity is thus placed on a pedestal, its historicity is restored and engaged in service to the former, while its architecturality is rendered at once an allegory and a framework of the dynamic, but extremely subtle, relationship between religion and history. Indeed, the realm of the Quba’ mosque is so vast and its individuality so generous that there was always room for embracing and treating fairly all the three ontological dimensions. The mosque was a bequest whose benefactions were inexhaustible. There are four chapters in the book. The first chapter is about the historical and religious significance of the Quba’ mosque, and how much, plus in what manner, the mosque has featured in the works of early Muslim visitors and scholars. A brief architectural history of the mosque is also presented. The second chapter delves into the issue of the Quba’ mosque as perceived by non-Muslim travellers and explorers, taking the legacies of John Lewis Burckhardt, as an “honest” and “accurate” Swiss, and Richard Francis Burton, as a “bigoted” and “militant” orientalist - as specimens. The third chapter discusses the roles and contributions of the latter Muslim visitors and explorers, concentrating on the subjects of the proliferation of Muslim hajj and holy cities literature, the scientific approach of Ayyub Sabri Pasha insofar as the theme of the Quba’ mosque was concerned, why some scholars and visitors were frugal in connection with reporting about the Quba’ mosque, the remarkable role of Ibrahim Rif’at Pasha as the commander of the Egyptian mahmal escort, and the case of Eldon Rutter set against the backdrop of the epoch of trials in Madinah. The fourth chapter deals with the providence of the Quba’ mosque after the arrival of the Saudis, discussing such topics as the advent of a new dawn or a modern era, John Philby and the period of transition, Lady Evelyn Cobbold and the commencement of some new trends relating to the Quba’ mosque, the instances of Muhyuddin Ridha and Jamaluddin al-Qasimi that reflected the emerging trends, and the modern Saudi renovation and expansion programs meant for the Quba’ mosque.